Assesment Tes Pada Hasil Belajar - Agus Sriyanto (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2019)
Abstrak The results of cognitive learning were assessed by test techniques through the items as instruments. A good instrument should have a good level of difficulty, a good differentiation of problems and have a well functioning distractor (when it comes to multiple-choice objective items). (1) The analysis of difficulty level is an opportunity to answer correctly a problem at a certain level of proficiency that is usually expressed in the form of indexes. The difficulty level function is associated with the test purpose. Difficulty level of problem can be done before or after test. (2) The distinguishing power is the ability of a question to distinguish between a capable student (mastering the material being asked) and an underprivileged student (not yet mastered the material being asked). Differentiation power can be found by looking at the large and small number of differentiator Power Index (IDP). (3) The analysis of the Distractor function is an analysis that is performed only on the objective of multiple choice models. Keywords :Analyze the difficulty level problem, problem differentiator, and analysis of distractors function.